Strategy for Adapting Licensing Services with the Online Single Submission Risk Based Approach (Oss-Rba) System in Madiun Regency - Setyawan, Erlangga; Utomo, Muhammad Tata Rizky Setyo; Rahma, Nabila Mafaaza (prodima@fe.uika-bogor.ac.id, 2024)
The Industrial Revolution 4.0 is changing human lifestyles, including digitally transformed ways of connecting and working. This opens up great opportunities for Indonesia and the government to innovate in carrying out their duties, with the hope that information technology can accelerate e-governance and technology-based public services. One of the initiatives resulting from this effort is an electronically integrated licensing system, Online Single Submission Risk Based Approach (OSS-RBA). However, the initial inspection of the Madiun Regency DPMPTSP on January 17 2023 showed problems in processing business permits online through OSS-RBA. When people face problems such as internet network disruption and system problems, they have to return to the service office. This research aims to find strategies for adapting OSS-RBA licensing services in Madiun Regency with a focus on improving internet-based performance and efficiency. The methodology includes situation analysis, e-governance requirements, and literature research on OSS-RBA in other areas. Obstacles such as the lack of integration between service systems which slows down the licensing process are also a concern. Adaptation strategies are proposed, such as improving internet network quality, system integration, and updating OSS-RBA. It is hoped that this strategy will increase the effectiveness of online licensing services and can be adopted in other regions in Indonesia. The conclusions of this research provide guidance for Madiun Regency DPMPTSP to improve online licensing services, supporting the growth of business actors in the region.